Energy scavenging from waste heat and electromagnetic induction: Tests and measurements - Dziurdzia, Piotr; Rodzen, Lukasz; Gorka, Dawid; Brzozowski, Ireneusz; Kos, Andrzej (ICSES 2014 : 2014 International Conference on Signals and Electronic Systems : Poznań, Poland, 11-13 September 2014, 2014)
The article deals with a subject of energy scavenging of small pieces of heat and vibrations by means of custom made energy converters. The harvested energy could be next used for powering battery-less microelectronic systems and Internet of Things components. The described customized transducers of waste heat and electromagnetic field were designed and tested. An ultra-low voltage converter and power management circuit was used during measurements. It made feasible to figure out the levels of available "free" ambient power. The paper provides discussion and conclusions after practical laboratory experiments.